Religion and Indigeneity at Yhyakh - Nikanorova, Liudmila (UiT Norges arktiske universitet, 2019)
Each summer in the Sakha Republic (Russia), hundreds of thousands of people celebrate an event called yhyakh. This dissertation explores articulations, performances, and translations of the concepts ‘religion’ and ‘indigeneity’ at and around contemporary yhyakhs. It focuses particularly on how yhyakh is understood and performed by its participants, on the motivations of the actors who promote different yhyakhs, and on a wide variety of circulating narratives. The study is ethnographic in method and based on fieldwork at and around the Tuymaada Yhyakh and the Olongkho Yhyakh from 2016 to 2018. Using articulation theory and heuristic models of religion-making and indigenous-making, the analysis unpacks how ‘religion’ and ‘indigeneity’ appear as descriptors, aspects, and parts of yhyakh. Yhyakh has attracted scholarly interest since the 17th century. This attention has only increased after the dissolution of the Soviet Union, as the celebration of yhyakh has expanded rapidly and become a major rallying point of the Sakha revitalization movements. In both historical and contemporary contexts, scholars have categorized yhyakh as, for example, a ‘shamanic ceremony’, a ‘religious ritual’, the ‘Sakha national day’, an ‘indigenous festival’. My ethnographic material reveals much broader variety of understandings of yhyakh, including ‘healing’, a ‘family holiday’, and a ‘day when Sakha feel Sakha’. By exploring how yhyakh and its practices are translated towards and away from ‘religion’ and ‘indigeneity’, not only by scholars but also by a wide range of other actors, I show how categorizing are powerful acts with far-reaching effects both for those who categorize and for that which is categorized.